An Evaluation of the Prevention and Combating of Corrupt Activities Act No 12 of 2004 - Pragal, Oliver (Institute of Criminology, 2014)
The present dissertation will firstly focus on analysing the universal structure and essential elements of the actual phenomenon of corruption. On this basis it will following be examined, which specific problems arise from this structure in respect of legislation that aims at combating corruption. Against this background the PCCAA will then be evaluated and commented. For this purpose also the offences against corruption as stipulated by the German Strafgesetzbuch (Penal code) will be taken into a comparative consideration.